2018
DOI: 10.4314/as.v17i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive urolithiasis in a 11/2 – year old Ouda–Yankasa ram: case report

Abstract: Obstructive urolithiasis is the retention of urine subsequent to the lodgement of calculi in the urinary tract from the kidney up to the urethral orifice. This report describes the post-mortem and chemical analysis findings of the calculi in an 18-month old Ouda-Yankasa cross ram presented at the Large Animal Clinic of the Veterinary Teaching Hospital, Usmanu Danfodiyo University, Sokoto. The patient was presented on 20th of March, 2013 with reports of anorexia, disinclination to drink water and anuria that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Tubular necrosis, ranging from mild to severe, was found in 78.57% (11/14) of lambs of both groups (22/28), which is a relevant finding for this study, corroborating other authors (25) , who reported this change as the most frequent, with 40% in the group that received urinary acidifiers and 70% in the control group. In a case report, this alteration in the histopathological analysis of an Ouda-Yankasa ram was also described along with glomerular atrophy (38) , which was not a common finding in the present study. Another study (37) reported, in addition to tubular and glomerular degeneration, fibrosis of the renal tissue in a Romanov sheep, which was not found in the lambs in this study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Tubular necrosis, ranging from mild to severe, was found in 78.57% (11/14) of lambs of both groups (22/28), which is a relevant finding for this study, corroborating other authors (25) , who reported this change as the most frequent, with 40% in the group that received urinary acidifiers and 70% in the control group. In a case report, this alteration in the histopathological analysis of an Ouda-Yankasa ram was also described along with glomerular atrophy (38) , which was not a common finding in the present study. Another study (37) reported, in addition to tubular and glomerular degeneration, fibrosis of the renal tissue in a Romanov sheep, which was not found in the lambs in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Although mild hydronephrosis and dilation of the renal pelvis were observed in two animals, in addition to a large abundance of stones, the kidneys were of normal size. Other authors (1,21,38) found alterations in sheep such as pyelonephritis and hydroureter, which were not observed here.…”
Section: Discussioncontrasting
confidence: 64%
“…N ephrolithiasis is one of the most important urinary tract diseases of ruminants and a costly problem for many sheep and goat owners (Makhdoomi and Gazi, 2013;Jones et al, 2017;Alimi et al, 2018). The urinary calculi etiology is complex and multifactorial that usually results from a combination of several nutritional, physiological and management factors (Constable et al, 2017;Smith et al, 2020).…”
Section: Introductionmentioning
confidence: 99%